Mapping the Preferences of Apple Consumption in Romania - Ionela Mițuko Vlad; Ana Cornelia Butcaru; Gina Fîntîneru; Liliana Bădulescu; Florin Stănică; Elena Toma (Horticulturae, 2022)
The fruit sector in Romania and, particularly, the apple production sector, is considered to have been in decline in recent decades. Changes in the behavior and consumption habits of the population, together with climate change and the increase in fruit imports, have caused shortages in this sector. Apples are regarded as a national fruit in Romania, but recently, there have been significant transformations in apple production and consumption. In order to practically observe the recorded information published in a database for this sector, we developed a questionnaire, which was completed by people in Romania. The aim of this paper was to identify the types of apple consumer profiles in Romania. The reason for choosing this specific fruit was linked to the investigated objective of the projects to which this article is related. Regarding the approached methodology, the paper focused on analyzing descriptive statistics, frequencies and clustering, by which means we designed a pattern of the apple consumer profiles in Romania. Furthermore, the profiles of respondents from two regions of Romania (South-Muntenia and South-East Regions) were explored in more detail. The findings of this research indicate a young, educated consumer profile and a distinct pattern revealed by the three clusters from the specific regions.